Cloud Computing For Supply Chain Management - Ms.Harshala Bhoir; Mrs.Ranjana Patil Principal (International Journal of Innovations in Engineering Research and Technology, 2021)
Cloud computing can give the ability of flexibly outsourcing softwarefor supply chain collaboration andinfrastructure needs in a better way. Instead of maintaining andpaying for maximum use this technology putsforward the method that provides flexibility to add on the way, dependingupon the overall business process andnetwork model of supply chain. Ahead of the usual technology publicity, theworth of cloud computing is that itcan be a right technology for supporting and managing a constantly changing and dynamic network and thus forsupply chain management. Because now a day these are the exactvisibility and supply chain collaborationneeds. Efficient supply chains are a vital necessity for many companies. Supply chain management acts onoperational processes, divergent and consolidated information flows andinteraction processes with a variety ofbusiness partners.